Prenatal screening of gestation. Intercurrent disease in pregnancy. - Rodríguez Luna, Roberto (2015)
Hypertensive disorders in pregnancy include those vascular diseases that exist before pregnancy and are complicated by the same, and vascular alterations that occur only during pregnancy and the immediate postpartum period in a woman who has been clinically well before. The fundamental nature of these disorders is hypertension. Increased blood pressure is often accompanied by edema, proteinuria, seizures and other manifestations, individually or in combination. These states usually called "preeclampsia", but today should be used less this name denotes That relationship of cause and effect of a circulating toxin. Since no one has discovered toxin, "toxemia" does not define portrays the clinical entity.